Turma Elizabeth Teixeira: um estudo de caso sobre o curso especial de bacharelado em direito para beneficiários da reforma agrária implementado na UEFS – 2012 a 2018 - Caldeira, Ariana Rocha (2019)
This research is a case study, objectified in the Class Elizabeth Teixeira - first class of higher education of UEFS and second class / course of Bachelor of Law of PRONERA. Through a qualitative study, systematized through interviews and documentary analysis, we analyzed the way legal knowledge is accessed by the field workers in the course, assisting them in the legal and political confrontation of the land struggle processes. For this we made a historical balance of the struggle for land and other fundamental rights, such as the right to education - specifically to the peasants. We underline the importance of the UEFS project in class solidarity, providing grassroots access to the University. The new lawyers now have a twofold task: (a) to confront the legal clashes in which it is becoming clearer and clearer that the law is flexible and bends to the strongest side of the correlation of forces at this time, economic power; (b) train workers to understand the typical injustices of capitalist relations of production, expanding class consciousness to themselves from the bottom up, from the peripheries. This last task is more important and more urgent. The tasks are ongoing: theorize the practice! Scientific (political-legal) knowledge has been apprehended and must be transposed to reality as reaffirmed by the research subjects. For this, it is necessary to use specific pedagogical tools and contextualized to the real needs of the rural / rural territory.